Kebebasan Beragama Perspektif Al-Quran (Telaah QS. Al-Baqara>h 256) - Andressa Muthi’ Latansa (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Every human being is free to choose a religion according to his religious experience and in accordance with his personal beliefs. Even Human Rights has been mentioned about basic human rights in detail, which one of them is freedom of interest and religion. The detail is also practised in Indonesia according to the 1945 Constitution (UUD) of the Republic of Indonesia, it is said that the state guarantees the freedom for the people to embrace the religion of their choice. Furthermore in Islam, it also regulates freedom of religion as mentioned in the alQuran. This paper will focus on how freedom of choosing a religion based on freedom in the al-Quran. Islam respects freedom in embracing any religion and belief.